1-(4-Chlorophenyl)-3-(2-thienylcarbonyl)thiourea - Saeed, Sohail (International Union of Crystallography, 2010)
The title compound, C(12)H(9)ClN(2)OS(2), exists in the thioamide form with an intramolecular N—H⋯O hydrogen bond across the thiourea and the carbonyl group. The dihedral angle between the rings is 10.36 (11)°. In the crystal structure, molecules are linked into chains by weak intermolecular C—H⋯Cl hydrogen-bonding interactions.